Pandangan barat dan Islam terhadap filsafat, ilmu, dan pengetahuan - Fianti, Riama Arda (Maliki Interdisciplinary Journal, 2024)
Different reflective thinking about problems related to the basic basis of science and the relationship between a science and all aspects of life is a philosophy of science. In science itself there are special sections in which there are objects, statements, sentences, and characteristics in science where these four aspects are in fact highlighted by three philosophical foundations of ontology, epistemology, and axiology. The method used in the journal uses literature study, literature study is a series to collect data in the journal in the form of collecting heritage data in accordance with the topic of discussion. This paper aims to describe science in terms of philosophy: ontology, epistemology and axiology, as well as Western and Islamic views on science. The results of the study can be concluded that ontologically we are practically discussing the nature of "what is". Science is seen through ontological by trying to find the truth and studying a science that can truly be proven. Epistemology discusses the basis of knowledge, sources, characteristics, authenticity of knowledge and how to obtain knowledge. Science is highlighted by epistemology, the discussion is focused on what are the sources used by scientists through the development of science and their methods. Axiology practically discusses the relationship between science and values. This results in axiology reporting ethically or not a science can develop.